Peritoneal dialysis in the Republic of Congo: history and current issues. (letter) - Eric Gandzali Ngabee; Judicael Kambourou; Cardinal Okiemy; Tony Daniel Eyeni Sinomono; Gael Mahoungou; Richard Loumingou (Bulletin de la Dialyse à Domicile, 2023)
Introduction